IDENTIFY AND PRIORITIZE EFFECTIVE FACTORS ON THE CUSTOMER SATISFACTION FROM SERVICE OF CREDIT SIM CARDS OF HAMRAH AVVAL OPERATOR USING KANO MODEL (Singaporean Journal of Business Economics and Management, 2015)
The expansion communication telecommunications networks and its acceptance to different aspects of human life, mobile communication many have been considered among the various industries. The advancement of technology and become more competitive environment of telecommunications industry, loyal customer is considered as the main asset each company, hence, firms to strengthen customer orientation to its products use the strategy of customer satisfaction. Also it is to identify their thoughts. This study takes action to identify and prioritize effective factors on the customer satisfaction from service of credit SIM Cards of Hamrah Avval operator using Kano model. This study in terms of purpose is applied and regarding the type is Descriptive-Survey that is done method of the field. Data collection tools in this study is the questionnaire with 30-item. The sampling is accessible non-possible and sample is included 192 patients credit SIM Cards subscribers of MCI corporation.The main purpose of this research is identifies and prioritize effective factors on the customer satisfaction from service of credit SIM Cards of Hamrah Avval operator. In the Kano model be identification factors of basic, motivational, and functional for each factor and ranking is done according to the customer satisfaction coefficient that is obtained for each of the 30 items. Results of this study show that each of the basic, motivational and functional requirements has impact on the customer satisfaction from service of credit SIM Cards of Hamrah Avval operator that conducted and concluded using T-Test.